Does improvement of environmental efficiency matter in reducing carbon emission intensity? Fresh evidence from 283 prefecture-level cities in China. (1st November 2022) - Ren, Yufei; Yuan, Wanruo; Zhang, Bitian; Wang, Shaojian
Abstract: While promoting environmental efficiency is widely perceived as one of the panaceas for solving environmental issues in China, little effort has been made to identify whether environmental efficiency improvement helps to reduce carbon emission intensity (CEI). Therefore, the work presented in this study remedies the inadequacies in the previous literature by investigating the linkages between environmental efficiency and CEI, by explicitly considering its spatiotemporal heterogeneous effect and dynamic measurement. We first measure the environmental efficiency (EE) and its growth (environmental total factor productivity) at prefecture level in China during 2003–2016 by incorporating a recently modified epsilon-based data envelopment analysis technique in the global Malmquist–Luenberger index. A spatial panel regression approach is then applied to reveal the impact mechanism of EE and its growth on the CEI. The empirical results confirm that promoting EE and environmental technology efficiency can help mitigate the urban CEI. However, the impact of economic scale efficiency on the CEI reduction has not been verified, indicating great room for CEI mitigation by optimizing the urban production scale and reducing production redundancy. Evidence from the spatiotemporal econometric analysis shows a spatially heterogeneous effect of EE on CEI, and the strength of influence tends to decrease over time. The findings also reveal that enhancing EE matters in reducing CEI for southern and western cities. Finally, several control variables have negative direct and indirect (spillover effect) effects on CEI reduction, including urbanization, industrial structure, and foreign direct investment. Our findings suggest that strengthening the synergistic effect between environmental pollution governance and carbon emission control by enhancing EE to promote low-carbon development in Chinese cities. Graphical abstract: Image 1 Highlights: An extended epsilon-based measure and global Malmquist–Luenberger index is proposed to measure environmental efficiency and its growth. Enhancing environmental efficiency has positive effects on CEI reduction in China. The technological progress change and pure technical efficiency change help to reduce CEI. The positive impact of environmental efficiency on CEI mitigation is gradually weakening. The impact of explanatory variables as well as their spatial spillovers on CEI are geographical heterogeneity.